The Impact of Distance Learning During the Corona Pandemic on the Mental Health of Primary School Students - Takash, Hanan M.; Al-Masa'deh, Mu'tasem M.; Al Momani, Wafa Abdullah (Journal of Ecohumanism, 2024)
This paper investigates the impact of distance learning, within the context of the COVID-19 pandemic, on the mental health of primary school students, as perceived by their parents. The critical factors examined in this paper include the use of technology, the lack of physical interaction between the students and the teachers, and whether adequate psychological support was provided to the students from school. It wants to explain how such variables influenced the emotional life of students, whether they developed anxiety or stress, had behavioral changes, or had much change in social interactions. A sample of 150 parents whose students were at the primary level of education and attended distance learning classes during the pandemic took part in the data collection. The structured questionnaire would be prepared to assess the parents' perception of their children's mental health. The items would range from a 3-point Likert scale addressing mental health and wellbeing, the influence of technology, and school support. The results of the present study indicated that, from the perspective of their parents, primary school students have been considerably affected mentally as a consequence of distance learning. The highest mean, 2.26, refers to increased anxiety and stress, which is very strong. Changes in behavior were moderate, as reflected by the mean of 2.11, and so was its impact on sleep at 2.01. With the advent of technology, stress levels went up, as shown by the strong correlation of 0.66, while technology influencing independent learning was negatively correlated at -0.46. Not having physical interaction with others greatly affected the mental health status of the students, as depicted by the mean of 2.31 and significant results in introversion: F-statistic 7.06 and p-value 0.0006. Moreover, more than 53% of parents felt that psychological support from schools needed to be increased, and 60.1% needed more recommendations for helping their children cope with the psychological burden of transitioning to remote learning.